What now? - Patchett, Ann (Harper, 2008)
An inspirational primer based on the author's 2006 commencement address at Sarah Lawrence College discusses how to manage life's crossroads, recounts times of struggle from her own life, and celebrates the benefits of not knowing what is to come.